Therapeutic value of voltage-gated sodium channel inhibitors in breast, colorectal and prostate cancer: a systematic review - Fabiola eMartin; Fabiola eMartin; Chiedu eUfodiama; Ian eWatt; Martin eBland; William J Brackenbury (Frontiers Media S.A., 2015)
Although survival rates of breast, colon and prostate cancers are improving, deaths from these tumors frequently occur due to metastasis. Voltage-gated Na+ channels (VGSCs) are membrane proteins, which regulate membrane current and cellular migration during nervous system organogenesis. VGSCs are also expressed in fibroblasts, immune cells, glia and metastatic cancer cells. VGSCs regulate migration and invasion of breast, bowel and prostate cancer cells, suggesting that they may be novel anti-metastatic targets. We conducted a systematic review of clinical and preclinical studies testing the effects of VGSC-inhibiting drugs in cancer. 204 publications were identified, of which two human, two mouse and 20 in vitro publications were included. In the clinical studies, the effect of these drugs on survival and metastatic relapse is not clear. The 22 preclinical studies collectively suggest that several VGSC-inhibiting drugs inhibit cancer proliferation, migration and invasion. None of the human and only six of the preclinical studies directly investigated the effect of the drugs on VGSC activity. Studies were difficult to compare due to lack of standardized methodology and outcome measures. We conclude that the benefits of VGSC inhibitors require further investigation. Standardization of future studies and outcome measures should enable meaningful study comparisons.